Cypriot Consumer Behaviour Towards Luxury Brands - Archeou, Maria (2008)
This study has been concentrating on the Cypriot market to discover the various factors that drives consumers to purchase luxury brands. A qualitative approach was used to conduct this research in order to gain insights over consumers' purchasing behaviour. Therefore, an interview method was chosen to gather the data needed.Initially, an interview with few managers of luxury brands in Cyprus was made to gather some information about the Cyprus market, their target segments profile and the way that luxury companies operate in that market. Afterwards, a snowball effect was used to gather a sample of ten consumer that purchase luxury handbags to be interviewed. In addition, the research was mainly based on three consumer behaviour theories: self concept, reference groups and symbolic interaction. These theories were the basis to enhance researcher's understanding over consumer behaviour and assist in analysing the data gathered. Moreover, a number of motivators and influences have been discovered from this study, where they were drawn in a model to provide a holistic view to marketing managers that target the Cypriot consumers. This model helps managers to gain insights of their target segments behaviour regarding luxury purchases, and guides them into which factors they should focus to develop more effective communication strategies.